Use of Outdoor Take and Give Games to Increase Students' Motivation to Learn English - Armanda, Jefferi; Iskandar; Fatmasari, Elly (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This research aims to increase motivation to learn English, especially speaking skills, for class X TKJ 1 at SMK Muhammadiyah Imogiri by implementing the Outdoor Take and Give Games learning model. The subjects of this research were 32 students in class X, TKJ 1. This action research consists of 3 cycles. The objects studied were students' learning motivation and students' English-speaking skills. This research uses data in the form of students' speaking test results, interview results, observation sheets, and questionnaires. Research activities include action planning, action implementation, observation, and reflection. The research results show that: (1) the outdoor take-and-give games learning model can make English learning more interesting and fun; (2) the outdoor take-and-give games learning model can increase students' motivation to learn English; and (3) the learning model of outdoor take-and-give games can help improve students' speaking skills. Therefore, this learning model can be used as an effective alternative activity in the learning process.